ANALYSIS OF PRODUCTION RISK AND INCOME OF SWEET CORN FARMING IN CAMPAGAYA VILLAGE, GALESONG DISTRICT, TAKALAR - Tri Pujiono (Institute of Computer Science (IOCS), 2022)
Sweet corn is a palawiji commodity that is much liked by the public. This commodity is a vegetable that can be used in a variety of foods. The many benefits of sweet corn in people's lives have resulted in the high demand for sweet corn for the community and the market opportunities are always wide open. The high demand for sweet corn from the wider community indicates that sweet corn productivity must be increased. One of the ways to increase productivity in terms of income can be done by calculating the production risk and income in sweet corn farming. This study aims to determine the risks that occur in the production and how much income sweet corn farming is. The method used is a population census of sweet corn farmers as many as 26 people, then a 100% sample is taken so that the sample is 26 people. Meanwhile, for production data analysis using coefficient of variation analysis and for sweet corn farming income using income analysis. The results of the study aimed at analyzing the production risk and income of sweet corn farming. Analysis of the risk of sweet corn production from the coefficient of variation (CV) of 0.017, meaning that sweet corn production has a low risk, while sweet corn farming income is Rp. 1,707.181.